EXPERIENTIAL LEARNING TO ENHANCE MOTHER TONGUE LANGUAGES (MTL) LEARNING IN SINGAPORE’S CONTEXT AMONG JC1 STUDENTS - A CASE STUDY OF BALESTIER CULTURAL TRAITS - Saphari, Nor Hanisah; Bakar, Makhfadzah Abu; Thiru, K; Hoe, Tan Kian (PEOPLE: International Journal of Social Sciences, 2015)
Singapore’s bilingual policy is implemented to cater to the needs of its multilingual population. While English is the official language, the other main ethnic languages namely Malay, Chinese and Tamil are termed as Mother Tongue Languages (MTL). Educators have been challenged to teach the MTL effectively amidst the rampant use of English among younger generation especially in the 21st century. Experiential Learning has been one of the strategies to enhance MTL learning among students who are learners of the 21st century. This study looks at how Experiential learning specifically a planned heritage trail-based trip can affect students’ learning and influence their perception of the MTL as a living language. This method has been useful and students’ appreciation towards the learning of MTL has also improved. Although Experiential Learning is found to be effective, more steps and initiatives need to be taken and adopted in order to realise the vision of the bilingual policy in Singapore and to prepare students face future challenges by equipping them with 21st century competencies.